Impact of residual stresses on mechanical behaviour of hot work steels. (December 2018) - Fajoui, Jamal; Kchaou, Mohamed; Sellami, Amira; Branchu, Samuel; Elleuch, Riadh; Jacquemin, Frédéric
Abstract: This paper presents a multi-scale analysis of the mechanical behaviour of hot work steels taking into account the effect of residual stress generated by the initial microstructure and the external load and induced industrially by heat treatment and machining process. The methodology is based on: i) laboratory study to evaluate the macroscopic behaviour of the material, ii) numerical simulation based on finite element and homogenisation approaches to evaluate the material's microstructure complexity and characterize the residual stress distribution, iii) industrial tests during pretreatment and forging process of valve gas parts in order to complete the results obtained at laboratory scale. It was proved that residual stress induced by the initial microstructure of the hot steel material has significant effects on the stress behaviour of the hot forging steel under static tensile load. Besides, the residual stress generated during the manufacturing process affected more significantly the stress distribution on the die surface than the heat treatment, inducing residual stress close to plastic deformation. Highlights: Experimental and numerical study of the stress behaviour of hot forging steel. Residual stress generated by the initial microstructure and the external load is analysed. Residual stress generated during the manufacturing process has more significantly effect on the die surface than the heat treatment.